Kohabitacja a trwałość gabinetów koalicyjnych w Polsce po 1991 roku - Banaś, Michał; Lechowicz, Piotr (Polityka i Społeczeństwo, 2021)
In relation to the systemic transformation, which began in Poland in 1989, there was a need to define a new political regime. Eventually it was decided to settle upon a system of government which is characterised by the duality of executive power exercised by the President, as well as Prime Minister and the government accountable to parliament. This element of the political regime creates the potential for cohabitation – an inherently conflictual phenomena which can have many negative consequences. One of them is the possibility of its negative impact on the duration of the coalition cabinet. In this article, we intend to test the hypothesis, according to which the phenomenon of cohabitation has a negative impact on coalition governments through the reduction of their duration. The aticle consists of four parts. The first briefly characterizes the evolution of the Polish political regime, highlighting the potential for cohabitation which is created by the dual structure of executive – the permanent element of Polish system of government. In the second part we explain the concepts of the cabinet government and the coalition. In the third section we describe coalition governments formed in Poland in the years 1991–2014 and the phenomenon of cohabitation occurring during their lifetime. In the fourth part we examine the impact of cohabitation on the duration of coalition governments in Poland. The conclusions of the analysis are presented at the end.